2016
DOI: 10.7314/apjcp.2016.17.4.1973
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Molecular Subtypes Defined by ER/PR and HER2 Status: Association with Clinicopathologic Parameters in Ivorian Patients

Abstract: Background: Breast cancer is a heterogeneous disease that represents a major public health problem. The immunohistochemical determination of breast cancer subtypes with regard to estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor (HER2) status can contribute to improved selection of therapy and patientcare. The purpose of this study was to determine the prevalence of the molecular breast cancer subtypes and to assess their associations with classical clinicopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
12
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
13
12
2
Order By: Relevance
“…In the present study, positive ER immunostaining was found in 54.7% of cases. Our result is similar to that reported by Effi in Ivory Coast [ 23 ]. However, our finding is lower than those reported in western countries [ 5 ] and Asia [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, positive ER immunostaining was found in 54.7% of cases. Our result is similar to that reported by Effi in Ivory Coast [ 23 ]. However, our finding is lower than those reported in western countries [ 5 ] and Asia [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Luminal B like (25.9%) and triple negatives (25.7%) were the commonest variety seen and overall Her2 positivity was seen in 30.1% of the patients. Luminal A-like disease with good prognosis is seen only is 18.3% of the cases which is in contrast to the figures from other areas reported to be 27.1% by Smriti Tiwari et al, 51.6% by Ahoua B Effect et al, Lin Ch 67% and it has been reported to be as high as 74.3% by Ahmed Abdel-Latif [10][11][12][13][14]. Luminal B like was the commonest type seen in our patients, like in Columbian women which were 37.2% [15].…”
Section: Discussionmentioning
confidence: 81%
“…The age of those in the ERBB2-positive group was not significantly different from the other 2 groups. The median age of the control group was significantly younger when compared with the other groups (30.5 years [range, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]). Two patients were lost during follow-up, and the remaining patients were followed-up for 23 to 50 months after surgical excision, with an average follow-up time of 41 months.…”
Section: Resultsmentioning
confidence: 99%
“…13,[23][24][25][26][27][28][29][30][31][32] The natural history, progression, and mechanism underlying DCIS are poorly understood, although several studies have shown that the transition from DCIS to invasive disease is associated with quantitative rather than qualitative differences in gene expression. 2,14,25,33 Biological markers to predict the presence of occult invasive disease or to identify patients at higher risk of developing invasive cancer are needed so that clinicians can better tailor the management of these lesions.…”
Section: Triple Negative Er/pr Erbb2mentioning
confidence: 99%